Intra-Annual Variation in Mesophotic Benthic Assemblages on the Insular Slope of Southwest Puerto Rico as a Function of Depth and Geomorphology - Appeldoorn, Richard S.; Ballantine, David L.; Carlo, Milton; Cruz Motta, Juan J.; Nemeth, Michael; Ruiz, Hector J.; Schizas, Nikolaos V.; Sherman, Clark E.; Weil, Ernesto; Yoshioka, Paul M. (Frontiers in Marine Science, 2021)
There is limited information on the intra-annual variability of mesophotic coral ecosystems (MCEs), worldwide. The benthic communities, measured as % cover, of two geomorphologically different mesophotic sites (El Hoyo and Hole-in-the-Wall) were examined during 2009–2010 in southwest Puerto Rico. Depths sampled were 50 and 70 m. At each site/depth combination, two permanent transects, measuring 10-m long by 40-cm wide, were surveyed by successive photoquadrants, 0.24 m2 in area. Scleractinian corals, octocorals, macroalgae, crustose coralline algae (CCA), sponges and unconsolidated sediment were the main components along the transects. Significant community differences were observed both among sites and among depths. Differences among sites were greater at 50 m than at 70 m. The El Hoyo site at 50 m was the most divergent, and this was due to a lower coral and sponge cover and a higher algal cover (Amphiroa spp., Peyssonnelia iridescens, turf) relative to the other site/depth combinations. As a consequence, the differences in community structure with depth were larger at El Hoyo than at Hole-in-the-Wall. The communities at 70 m were distinguished from those at 50 m by the greater proportion of the corals Agaricia undata, Madracis pharensis and CCA, and a reduced cover of the cyanobacterium Schizothrix. Temporal variation in the benthic assemblages was documented throughout the year. For both mesophotic sites, the magnitude of change at 50 m was significantly greater than at 70 m. For both depths, the magnitude of change at El Hoyo was significantly greater than at Hole-in-the-Wall. All assemblages experienced almost the same temporal patterns, despite the differences in species composition across sites and depths. Changes in temporal patterns are driven by an increase in the percent cover of the macroalgae Dictyota spp., and a decrease in the percent cover of non-colonized substrata (sand, pavement or rubble). Relatively rapid, intra-annual changes are dictated by the negative correlation between cyclic Dictyota spp. cover and open substrata cover. Other observed mechanisms for rapid community changes in the photoquadrants were diseases and collapses of substrata along with their associated fauna indicating that small-scale disturbance processes may play an important role within MCEs.